MANUSKRIP MUSHAF AL-QUR’AN ISMAHAYANA, KABUPATEN LANDAK (Sebuah Studi Awal Tentang Aspek Kodikologi) - Rini Kumala Sary; Wajidi Sayadi (IAT IAIN Pontianak, 2021)
Abstract This study discusses about codicology on the manuscripts of the Qur'anic contained in the Ismahayana palace, Landak district. Then this manuscript was named the Ismahayana Manuscript. This manuscript was handwritten by the deputy king of the Ismahaayana Landak palace, namely King Pangeran Mangku Gusti Bujang (1899–1922). The method used is a qualitative method and this type of research is an analytical description, and considering the object of study is the Qur'anic Manuscript, the data collection is based on the facts found in the field. This study was conducted using a philological approach, focusing on two main topics. First, about the characteristics of the Qur'anic manuscripts. Second, how are the codicological aspects contained in the manuscript of the Al-Qur'an Ismahayana Landak manuscript. The conclusion of this article is that the use of rasm in the manuscript of the Qur'anic manuscripts contains two rules, namely the Ottoman (Utsmani) rasm and the imla'i rasm. While Scholia is divided into two, namely scholia to maqra and scholia to juz. This manuscript is proof that the copying process was carried out by handwriting and rote memorization. As proof that there are errors in the writing and placement of vowels. Furthermore, the use of this manuscript paper still uses cardboard from bark because each sheet of manuscript still feels wood grain and the binding is from bark, and there is a logo on one of the manuscript sheets which proves that the Qur'an is indeed from the Ismahayana Landak palace.